Treatment of polluted river water using potential bioflocculant produced by Klebsiella pneumonia UKD24 - Kaarmukhilnilavan, R S (Environmental technology, 2024)
Chemically enhanced primary treatment (CEPT) is a rapid wastewater treatment process involving treating wastewater with two chemical-aided processes, coagulation, and flocculation. In the present study, a natural extracellular polymeric substance flocculant (EPSBF) produced by Klebsiella pneumonia UKD24, a bacterium isolated from the sewage treatment plant, and a synthetic polyacrylamide anionic polymer flocculant (PAM) were evaluated to treat polluted river water. The synthetic PAM showed immediate turbidity reduction after agitation, while the EPSBF expressed a rapid decrease in optical density. After 20 min of the settling period, the EPSBF showed reduced rates of turbidity, optical density, and chemical oxygen demand at 74.14 ± 5.2%, 89.37 ± 0.76%, and 87.21 ± 0.73%, respectively, while PAM showed 67.08 ± 4%, 85.68 ± 2%, and 86.57 ± 2%, respectively. EPSBF treatment significantly improved the water quality parameters in terms of total dissolved solids, total suspended solids, conductivity, and oxidation-reduction potential than PAM treatment. However, the EPSBF has shown a more water-holding capacity and relatively weak flock formation, producing more sludge volume than PAM. Furthermore, though the sludge produced by the EPSBF treatment had a higher moisture content, it showed shorter capillary suction time (CST). In contrast, sludge formed in PAM treatment had lower moisture content, but it exhibited prolonged CST value indicating that PAM treatment sludge showed slow dewaterability